Inhibition Kinetics of Sida rhombifolia L. Extract Toward Xanthine Oxidase by Electrochemical Method - Dyah Iswantini; Muammar Yulian; Sri Mulijani; Trivadila Trivadila (Indonesian Journal of Chemistry, 2014)
Sida rhombifolia L. is a traditional medicinal plant that has been known with potential as antigout. The previous research suggested that flavonoids crude extract of S. rhombifolia had an inhibitory activity toward xanthine oxidase by 71% and a spectrophotometric measurement showed that the type of flavonoids crude extract inhibition was a competitive inhibition. The purpose of the research was to investigate the type of inhibition kinetic of S. Rhombifolia’s ethanol extract by electrochemical method and to compare the measurements of linearity and sensitivity between spectrophotometric and electrochemical methods. The results showed that the yield of S. Rhombifolia’s ethanol extract was 9.82% with the inhibitory activity ranging from 13.64% to 82.69% (5.00-200 mg L-1) and IC50 value was 91.15±5.74 mg L-1. Allopurinol as a control showed the inhibitory activity of 15.26-70.95% (0.10-4.00 mg L-1) and IC50 value was 2.45±2.21 mg L-1. Inhibition kinetics of the ethanol extract caused a KM increase and unchange of VMAX. Based on the data, the type of inhibition kinetics was a competitive inhibition, with an inhibitor affinity (α) value of 3.18. Linearity of xanthine oxidase activity assay by electrochemical and spectrophotometric methods showed the range of 0.01-1.00 mM (R2 = 0.978) and 0.05-0.70 mM (R2 = 0.977) respectively. The sensitivity of electrochemical method was reported higher (0.95 μA mM-1) than the spectrophotometric method (0.007 min-1).